Aldehyde Dehydrogenase 1B1 as a Modulator of Pancreatic Adenocarcinoma. Issue 1 (January 2016) - Singh, Surendra; Arcaroli, John J.; Orlicky, David J.; Chen, Ying; Messersmith, Wells A.; Bagby, Stacey; Purkey, Alicia; Quackenbush, Kevin S.; Thompson, David C.; Vasiliou, Vasilis
Abstract : Objectives: The aim of the current study was to examine expression and the role, if any, of aldehyde dehydrogenase (ALDH)1B1 in pancreatic adenocarcinoma. Methods: A tissue microarray of 61 pancreatic cancer patients were evaluated for protein expression of ALDH1B1 by immunohistochemistry. The ALDH1B1 small interfering (RNA) was used to assess the contribution of ALDH1B1 on proliferation of pancreatic cancer cells. Results: In normal human pancreas, ALDH1B1 is abundantly expressed in glandular cells, but sparsely in the ducts (ALDH1B1 immunopositivity = 16.7 ± 1.7). In pancreatic ductal carcinoma, we found high ALDH1B1 expression in ductal cancerous tissues (ALDH1B1 immunopositivity = 197.2 ± 29.4). Analysis of ALDH1B1 expression in a human pancreatic adenocarcinoma tissue microarray showed the greatest expression in tumors that were more invasive. A variation in ALDH1B1 expression was also observed in 16 human pancreatic cancer cell lines. Knockdown of ALDH1B1 caused a 35% reduction in cell growth in the high ALDH1B1-expressing cell lines. Conclusions: Our data show for the first time that ALDH1B1 is expressed at very high levels in human pancreatic cancer, and it contributes to proliferation in these tumor cells. These data suggest a potential modulatory role for ALDH1B1 in pancreatic cancer.